Impact of early rehabilitation on Weber B ankle fracture anti-glide plate osteosynthesis - Peláez Alfonso, Libardo; Reina, Eduardo; Rangel, Carlos; Reyes, Óscar Eduardo; Herrera, Juan Manuel (Revista Colombiana de Ortopedia y Traumatología, 2016)
Introduction: Weber B ankle fractures are the most common fractures at the ankle joint and constitute the second cause of disability preceded only by ankle sprains. Surgical management of this fracture with posterior anti-glide plate technique allows the initiation of an early rehabilitation. Materials and methods: A prospective study was made, including 14 patients that underwent surgery with posterior anti-glide plate and subsequent management with early rehabilitation protocol designed by the Department of Physical Medicine. Results: The estimated time of disability in the study group was 55.3 days (SD = 10.11) That means 51 days. This is considered favorable when we consider a rehabilitation processes over 100 days reported in specialized literature. Discussion: Anti-glide plate osteosynthesis as well as the rehabilitation protocol should be considered as comprehensive treatment that can positively impact patient overall recovery by reducing disability in Weber type B ankle fractures. Evidence level: IV.